Using Sherrod Model Indicators to Predict Financial Failure: Applied Research in the National Company for Tourism Investment in Iraq for the Period (2016-2021) - Sameer Taha Yaseen; Shahad Mofaq AL-Hmadane (Kurdish Studies, 2024)
The study aims to use the indicators of the Sherrod model to predict the failure of tourism companies in Iraq, in order to take preventive measures to avoid financial failure that the company may be exposed to during a certain period, to be able to get the appropriate alternatives to avoid its occurrence, the study model Sherrod was applied to the National Company for Tourism Investment in Iraq based on the financial statements of the company's financial statements for the period from 2016 to 2021, the results were satisfactory, as the study found that the company is not prone to financial failure during that period, due to the high value of the quality index Z from 25 this is evidence of its distance from the problems of financial failure.